Self-Disclosure of Bumble Dating App Users in Building Friendship Relationships - Talia, Sefila Ananda; Nurnisya, Frizki Yulianti (Jogjakarta Communication Conference (JCC), 2023)
Online dating apps have changed how people find dates, from face-to- face to online meetings. One such online dating app is Bumble. Bumble users engage in online interactions, such as exchanging personal information as a relationship development process, before they meet face to face. This study discusses the self-disclosure of Bumble users using qualitative methods using social penetration theory. The results of this study found that through four different subjects with a constant and stable intensity, only one informant can express themselves better.